2010
DOI: 10.1002/ange.201001625
|View full text |Cite
|
Sign up to set email alerts
|

Oligomers and Cyclooligomers of Rigid Phenylene–Ethynylene–Butadiynylenes: Synthesis and Self‐Assembled Monolayers

Abstract: Ausgehend vom gleichen Bisacetylen entstanden abhängig von den Reaktionsbedingungen (Palladium‐ oder Kupferkatalyse) selektiv cyclische oder acyclische Oligomere mit n=2–6 (siehe Bild für den Fall n=3), die durch frei rotierende Eckstücke verknüpft sind. Aus STM‐Bildern der selbstorganisierten Monoschichten folgt der Unterschied im Adsorptionsverhalten der acyclischen und cyclischen Oligomere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
1
5
0
1
Order By: Relevance
“…The syntheses of the linear phenylene-ethynylene-butadiynylenes, the narrower half-ring structures (based on m- , m ′-, and m′′ -terarylene and m- , p ′-, m′′ -, p ′′′-, m ′′′′-quinquearylene building blocks), as well as the cyclic and acyclic oligomers of the respective half-rings have been described before. , Similar syntheses (involving m- , p ′-, p′′ -, m ′′′-, p ′′′′-, p ′′′ ′′ -, m ′′′′′′-septiarylene clamps) were applied to prepare the rigid rods and half-ring structure 3 . Details are given in the Supporting Information (SI).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The syntheses of the linear phenylene-ethynylene-butadiynylenes, the narrower half-ring structures (based on m- , m ′-, and m′′ -terarylene and m- , p ′-, m′′ -, p ′′′-, m ′′′′-quinquearylene building blocks), as well as the cyclic and acyclic oligomers of the respective half-rings have been described before. , Similar syntheses (involving m- , p ′-, p′′ -, m ′′′-, p ′′′′-, p ′′′ ′′ -, m ′′′′′′-septiarylene clamps) were applied to prepare the rigid rods and half-ring structure 3 . Details are given in the Supporting Information (SI).…”
Section: Resultsmentioning
confidence: 84%
“…The STM results obtained in our previous work showed that neither the unit cell vectors, a and b , nor the direction of the linear rigid units were oriented along the HOPG main axes . The adlayer orientation of the compounds relative to the underlying substrate could be understood only if the alkoxy side chains were assumed to be oriented along one of the HOPG symmetry main axes.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although a mean width of 20 nm is detected for the anisotropic 6 nm high aggregates in Figure b−e, the lateral dimensions of such small features are typically overestimated due to tip convolution. , Additionally, in some cases (as pointed out in Figure d, which is a detail image of Figure c with decreased z -scale) the tubes are lying on a monolayer of densely packed stripes with a height of 2 Å and a periodicity of 6 ± 0.2 nm. We attribute the latter to a self-assembled monolayer of 1D aligned flat-lying macrocycles (i.e., macrocycle backbones parallel to HOPG surface), which exhibit lateral phase separation where stripes of backbones appear to be separated by stripes containing the PS side chains (compare model shown in Figure f) . Conclusively, we assume that the anisotropic features in Figure b−e are individual tubes of 2a and bundles of a few parallel-aligned tubes (which are undistinguishable by AFM).…”
Section: Resultsmentioning
confidence: 85%
“…Schon seit längerem synthetisieren und untersuchen Chemiker am Kekulé‐Institut der Universität Bonn formtreue Makrocyclen und verwenden dabei die traditionsreiche Glaser‐Kupplung zum Ringschluss. Mit diesem Ziel wurde auch die oxidative intermolekulare Kupplung des gewinkelten Bisacetylens 2 sowohl Cu‐ als auch Pd‐katalysiert durchgeführt 7. In beiden Fällen wurden die Oligomere bis zum Hexamer mit der recGPC separiert und untersucht.…”
Section: Ergebnisse Für Gewinkelte Und Cyclische Oligomereunclassified